Detecting bioluminescence with an irradiance time-depth recorder deployed on southern elephant seals - Campagna, Claudio; Dignani, Jorge Pablo; Blackwell, Susanna B.; Marin, Maria Rosa (Marine Mammal Science)
While at sea, elephant seals (Mirounga spp.) spend 90% of their time underwater, at mean depths of 400-500 m while foraging during both daytime and nighttime (Le Boeuf 1994). Although most surface light is lost before reaching these depths, elephant seals have adaptations to low light levels that suggest visual predation. They have large eyes with a wide range of pupillary dilation (Levenson and Schusterman 1997), rapid adjustment to darkness (Levenson and Schusterman 1999) and a retina that has a peak sensitivity shifted to the blue-green (Lythgoe and Dartnall 1970, Carlson and Le Boeuf 1998). At depths where seals spend most of their time, bioluminescence is the main source of light. Fil: Campagna, Claudio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina Fil: Dignani, Jorge Pablo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina Fil: Blackwell, Susanna B. University of Stanford; Estados Unidos Fil: Marin, Maria Rosa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina